Lunger : the Doc Holliday story : a novel [large type] - Colt, Paul (THORNDIKE PRESS LARGE PRINT Softcover Western, 2024)
"The product of an aristocratic Old South upbringing, John Henry "Doc" Holliday's dreams of a career in dentistry are dashed at a young age by respiratory disease. Encouraged to seek the therapeutic benefits of drier climes, John Henry undertakes an odyssey crossing the western frontier, often in the company of soiled dove Kate Elder. It's a journey that transforms him from gentleman dentist to professional gambler. What emerges is a complex character we come to know through contrasting lenses-a family portrait protective of its legacy, a turbulent romantic relationship, and a friendship steeped in loyalty no matter the cost, all the while stalked by the specter of death riding a pale horse. Gambling, drinking, and living on the edge, ever beset by disease, Doc nevertheless maintains an inbred code of honor to violent necessity. He meets and befriends Wyatt Earp, following him from Dodge City in its wide-open, cow town heyday to a date with destiny in Tombstone. Ever trailing in Doc's wake, Kate is never far behind, her love drawn to the self-destruction of a condemned man, like a moth to the flame of inevitable demise. Doc walks away from the legendary O.K. Corral gunfight. He survives the Earp vendetta ride. He escapes legal consequences of the killings in Tombstone. But he can never outrun the rider mounted on a pale horse. Dancing on the edge of oblivion, driven by fate and an unyielding will to live on his own terms, Lunger is Doc Holliday's story as he himself might have told it"--